Highlight of primary and secondary relaxations in amorphous stereocomplex polylactides - N. Varol; X. Monnier; L. Delbreilh; A. Saiter; K. Fatyeyeva; E. Dargent (eXPRESS Polymer Letters)
A racemic mixture of two stereoregular polylactides (PLAs) (i.e. PLLA and PDLA) allows obtaining wholly amorphous stereocomplex PLA films by solvent casting method. The amorphous phase behavior of stereocomplex PLA is compared with that of PLLA and PDLA by advanced thermal analysis, such as Fast Scanning Calorimetry (FSC) and Dielectric Relaxation Spectroscopy (DRS). FSC allows us to quench at very high cooling rate (up to 4000 K・s–1) the studied polymers and to obtain glassy amorphous phases with high excess of enthalpy. It is shown that stereocomplexation has no influence on the glass transition temperature, the physical aging and on the cooperativity. The α and β processes were examined to study the dielectric properties, such as relaxation time, dielectric strength, and fragility. The results of FSC and DRS are correlated to determine the values of cooperativity length which are found to be similar in a wide temperature range. It is found that the studied polymers have the similar dielectric properties independently on their tacticity.